Milk lactose hydrolysis in a batch reactor:: Optimisation of process parameters, kinetics of hydrolysis and enzyme inactivation - Sener, N.; Apar, D. Kilic; Demirhan, E.; Ozbek, B. (CROATIAN SOC CHEMICAL ENGINEERING TECHNOLOGY, 2008)
The present investigation describes the effects of the process parameters on enzymatic hydrolysis of milk lactose and enzyme stability. The lactose hydrolysis reactions were carried out in 250 mL of milk by using a commercial beta-galactosidase produced from Kluyveromyces marxianus lactis. The residual lactose mass concentration and residual enzyme activity (%) against time were investigated vs. process variables such as temperature, impeller speed and enzyme concentration. Optimum conditions for hydrolysis were obtained as T = 37 degrees C, n = 300 rpm, sigma = 1 mL L(-1) enzyme concentration and 30 min of processing time. The lactose hydrolysis process resulted in 84 % of hydrolysis degree and 52 % of residual enzyme activity at the optimum experimental conditions obtained. After evaluation of the data, it was found that the kinetics of hydrolysis and enzyme inactivation could be represented by a first order kinetic model and a single-step non-first-order enzyme inactivation kinetic model for all process conditions applied. Also, to illustrate the effect of process variables on hydrolysis and enzyme stability, some modelling studies were performed. The activation energy for hydrolysis reaction (E(A)) was calculated as 50.685 kJ mol(-1).
Keywords: lactose hydrolysis; milk; beta-galactosidase; modelling; process variables; IMMOBILIZED BETA-GALACTOSIDASE; ESCHERICHIA-COLI; SKIM MILK; SUPPORTS; PRODUCTS; FRAGILIS; Biotechnology & Applied Microbiology; Engineering